Analysis of Maturity Level Project Management of Software Development In Scrum Framework: Case Research On Tribe Enterprise PT. XYZ - Fakhrul Ridha; Ega Hegarini (IT Journal Research and Development, 2020)
One of the most widely used product developments now is Agile Development Method. In Agile Development there are several frameworks, one of them is Scrum. This research examines the maturity level of software development project management that applies Scrum framework. The research was conducted using quantitative research methodologies using Scrum Maturity Model. Data was collected by distributing questionnaires to employees at a company that works as a Scrum Master. In addition to the data obtained from the questionnaire, interviews were also conducted to confirm answers from respondents. The interview aims to ensure the answers given by respondents are consistent with documentary evidence carried out through the research of project documents. Then the data analysis is done by assessing the level of maturity of each process in the Scrum framework using Agile Maturity Model (AMM) approach. The results from the analysis of Maturity Level Project Management of Software Development are used to provide recommendations for improvement to achieve a higher level of maturity.